Spinco Model 116 Amino Acid Analyzer - Illig, Russell (1960)
First marketed in 1960, the Beckman/Spinco Model 120 Amino Acid Analyzer allowed users to quickly perform amino acid chromatography. The Model 116 was a more modular instrument, marketed to customers with lighter workflows.
Keywords: Medical laboratories--Equipment and supplies; Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Amino acids--Analysis; Beckman Instruments, Inc.